Moral Values Reflected Through Linguistic Expressions in The Greatest Showman - Muhammad Regi Iswara Putra; Otong Setiawan Djuharie (Journal of Literature Review, 2026)
This study aims to reveal the moral values reflected through linguistic expressions in the film The Greatest Showman. The research focuses on analyzing dialogues and song lyrics that convey moral messages such as inclusivity, courage, self-acceptance, and resilience against social discrimination. The study applies a qualitative descriptive method using content analysis techniques. The data consist of selected utterances and lyrical expressions analyzed through pragmatic and discourse analysis frameworks. The findings show that the linguistic expressions found in the film demonstrate evaluative, affirmative, and persuasive forms that strengthen the delivery of moral messages. Language functions as a strategic tool for constructing moral discourse, encouraging audiences to embrace diversity, value equality, and appreciate individual identity.